Como o preço do livro influencia a formação de leitores - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This work focuses on the relationship between book prices and reader development in Brazil. The research begins with the question of how the value of literary works can hinder the democratization of reading, considering the economic, social, and cultural factors that influence this process. The research is qualitative and characterized as bibliographic, based on data, studies, and reports that address reading behavior and the conditions of access to reading in the country. The theoretical discussion considers reading as a social practice and a human right, linking it to the importance of public policies and libraries in expanding access to books. The study seeks to contribute to reflection on the relationship between book prices and reader development in Brazil, highlighting the importance of understanding the economic, social, and cultural factors that influence access to reading. The research reinforces the need to promote books as cultural assets and to encourage public policies aimed at expanding reading opportunities and strengthening reader development in the country. Keywords: Reading, book, training, price, democratization.
Keywords: Leitura; Livro; Livros - Preços; Democratização; Books - Prices; Reading; Book; Democratization; LINGUISTICA, LETRAS E ARTES